Neo-traditional salafi Qur’an-Sunna hermeneutics and its interpretational implications - Duderija, A. (Blackwell Publishing Ltd, 2011)
The purpose of this article is to outline the delineating features of a Qur’an-Sunnah hermeneutic of one of the contemporary Muslim schools of thought, here named Neo-traditional Salafism(NTS).The first section of the article provides a brief discussion of the main representatives of NTS. In the second part NTS is positioned in relation to the broader Islamic tradition. This is done so with respect to the relative status and authenticity of various sources of legal authority in the Islamic tradition and with a special attention given to the concept of Sunna. In the third part of the article NTS’ Sunna hermeneutic is examined more closely and its interpretational implications are noted. The fourth section describes the NTS approach to Qur’anic hermeneutics and its interpretational implications. The author argues that in terms of their methodology of interpretation of the Qur’an-Sunnah NTS is closely related to that of the pre-modern ahl-hadith school of thought as both NTS and ahl-hadith hermeneutic are characterized by a philologically centred interpretational orientation; textual ‘intentionalism’, i.e. the subscription to a voluntaristic view of law, ethics, morality and ontology; the belief in the fixed, stable nature of the meaning of the Qur’anic text residing in totality in the mind of its Originator, the interpretational marginalization of Qur’anic revelationary background; a ‘voluntarist–traditionalist’ view of the relationship between reason and revelation; textual segmentalist approach to the Qur’anic content and the illegitimacy of a hermeneutically priviledged aims (maqasid) and social benefit (maslaha) based approach to Qur’anic interpretation.